2006
DOI: 10.1094/pd-90-0115a
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Grapevine Declines and First Report of Black Dead Arm Associated with Botryosphaeria obtusa in Lebanon

Abstract: Grapevine, cultivated mostly in the Bekaa Plain, is one of the most important fruit crops in Lebanon. During July 2004, a survey was made in 11 vineyards of local table or wine grapes to evaluate the sanitary status of the grapevine industry as far as wood declines are concerned. The most common grapevine decline was esca. The two forms of the disease (mild and severe) were observed. The mild form was characterized by leaf symptoms consisting of interveinal necrotic spots with yellow or red chlorotic blotches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…The trunk disease fungi found in this study were similar to the preliminary results reported in Lebanon (Choueiri et al, 2006) and with the results reported in Europe and in other Mediterranean countries (Armengol et al, 2001;Aroca et al, 2006;Larignon and Dubos, 1997;Luque et al, 2009;Mugnai et al, 1996;Péros et al, 1999;Péros et al, 2008;Rumbos and Rumbou, 2001) as well as in Africa (Berraf and Péros, 2005;White et al, 2011). The current study sampled from a larger area including the main grapevine growing areas such as West Bekaa, Central Bekaa and North Lebanon and the isolations were more comprehensive than those conducted by Choueiri et al (2006). New reports for fungal species on grapevines include D. mutila, N. parvum, B. dothidea as well as Pm.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The trunk disease fungi found in this study were similar to the preliminary results reported in Lebanon (Choueiri et al, 2006) and with the results reported in Europe and in other Mediterranean countries (Armengol et al, 2001;Aroca et al, 2006;Larignon and Dubos, 1997;Luque et al, 2009;Mugnai et al, 1996;Péros et al, 1999;Péros et al, 2008;Rumbos and Rumbou, 2001) as well as in Africa (Berraf and Péros, 2005;White et al, 2011). The current study sampled from a larger area including the main grapevine growing areas such as West Bekaa, Central Bekaa and North Lebanon and the isolations were more comprehensive than those conducted by Choueiri et al (2006). New reports for fungal species on grapevines include D. mutila, N. parvum, B. dothidea as well as Pm.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, this is the first study using this classification method before microbial examination. The importance of grapevine in the Lebanese economy and the presence of trunk decline diseases in this country (Choueiri et al, 2006) have stimulated this survey. It also allowed us to observe the development of foliar esca symptoms (data not shown) during the summer of 2006 and to further demonstrate that leaf symptoms previously attributed to black dead arm (according to the description made by Larignon et al, 2001) in Lebanon (Choueiri et al, 2006) had been actually confused with those of esca (Lecomte et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Ascomycota Cladosporiaceae E, P, S ■; ▲; ● 0.5; 9.1; 0.2 [ 28 , 88 ] Cladosporium sphaerospermum Ascomycota Cladosporiaceae P, S 1.1 [ 88 ] Cryptococcus sp. Basidiomycota Cryptococcaceae E, S ■; ▲; ● 0.3; 2.8; 0.2 [ 28 , 92 ] Diplodia seriata Ascomycota Botryosphaeriaceae E, P, S ■; ▲ 0.2; 0.3 [ 78 , 79 , 82 , 88 , 91 , 92 , 94 , 97 , 98 , 102 , 104 , 108 , 123 , 124 , 125 , 126 , 127 , ...…”
Section: Figure A1mentioning
confidence: 99%